Dental Treatment Consideration in Pregnant Women - I Komang Evan Wijaksana (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Pregnancy is a unique time in a woman’s life, accompanied by a variety of physiologic, anatomic and hormonal changes that can affect how oral health care is provided. Good oral health during pregnancy is important to the overall health of both the expectant mother and her baby. Unfortunately, there may be times when pregnant women and family, obstetricians and on occasion dentists are skeptical of dental care during pregnancy owing to prejudices about the safety of dental treatment, resulting in delay of the dental treatment. This article aims to review general considerations of pregnant patients’ dental treatment, and possible dental complications of pregnancy and their management. Search for information through google scholar with the keyword’s “pregnancy” and “dental treatment